2009
DOI: 10.1017/s0317167100006600
|View full text |Cite
|
Sign up to set email alerts
|

Resiniferatoxin Mediated Ablation of TRPV1+ Neurons Removes TRPA1 as Well

Abstract: 234Mammalian temperature sensors of the transient receptor potential (TRP) family are tetrameric 6-transmembrane cation channels gated by heat, cold, as well as either endogenous or exogenous agonists 1,2 . The vanilloid receptor (VR1/TRPV1) is a non-selective ligand-gated Na + /Ca 2+ -channel [3][4][5][6] . TRPV1 is selectively activated by heat above 42ºC, pH < 6.3 7 , endogenous lipid mediators such as anandamide and oleoylethanolamide 4,8,9 , intracellular signaling molecules 10,11 and plant toxins, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 55 publications
7
40
0
Order By: Relevance
“…17, 20, and 21;Story et al, 2003;Kobayashi et al, 2005). Ablation of TRPV1 + neurons by RTX in mice results in an almost complete loss of sensitivity to allylisothiocyanate, a TRPA1 agonist (Pecze et al, 2009). These data support a high degree of colocalization between TRPV1 and TRPA1 in sensory neurons.…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 54%
“…17, 20, and 21;Story et al, 2003;Kobayashi et al, 2005). Ablation of TRPV1 + neurons by RTX in mice results in an almost complete loss of sensitivity to allylisothiocyanate, a TRPA1 agonist (Pecze et al, 2009). These data support a high degree of colocalization between TRPV1 and TRPA1 in sensory neurons.…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 54%
“…Given the potential role of TRPV1-expressing sensory neurons in the regulation of intestinal tumorigenesis, we also evaluated the phenotype of Apc Min/+ mice that underwent systemic ablation of TRPV1 + neurons. Apc Min/+ mice were treated with the ultrapotent TRPV1 agonist resiniferatoxin (RTX) during the neonatal period (47). Ocular challenge with capsaicin (eye wipe test) confirmed systemic TRPV1 + sensory neuron ablation.…”
Section: Egfr and Trpv1 Are Part Of A Homeostatic Molecular Circuitmentioning
confidence: 99%
“…To further explore the role of TRPV1-positive fibers in the antinociceptive effect of ␣-spinasterol in the paw reaction test to a heat stimulus, animals were submitted to a systemic desensitization protocol with RTX as described previously (Pecze et al, 2009). Pecze et al (2009) previously demonstrated that 50 g/kg s.c. of RTX largely reduced the expression of TRPV1 as well as increased noxious heat latencies and abolished capsaicin-induced eye irritation 7 days after treatment in adult mice. Moreover, they also observed that greater doses of RTX caused mice mortality.…”
Section: In Vivo Screening Of Trpv1 Antagonistsmentioning
confidence: 99%